TaqdÄ«m Al-Qiá¹£á¹£ah Program Management at An-Nur Islamic Boarding School in Surabaya - Zulfa Ainur Rohmah; Zakiyah Arifa (Jurnal Alsinatuna, 2019)
This study aims to determine the planning, organizing, actuating, and supervising the taqdÄ«m al-qiá¹£á¹£ah program at the An-Nur Islamic Boarding School in Surabaya. This type of research used in this research is descriptive qualitative. Sources of data in this study were divided into two kinds, namely primary data and secondary data. Data collection techniques used are interview, observation and documentation. Data was analysed by Milles and Huberman, through three steps, namely data reduction, data presentation, and concluding. The result showed that planning, organizing, actuating, and supervision of the taqdÄ«m al-qiá¹£á¹£ah program at the An-Nur Student Pesantren has been going well. This is proven by the breakdown of activities following the stated objectives.